Arterial Stiffness is Associated With Diabetic Retinopathy in Korean Type 2 Diabetic Patients - Yun, Yong-Woon (The Korean Society for Preventive Medicine, 2011)
OBJECTIVES: We evaluated the association between common carotid artery intima-media thickness (CCA-IMT), brachial-ankle pulse wave velocity (baPWV), carotid plaque, and peripheral arterial disease (PAD) as indicators of macroangiopathy and diabetic retinopathy as an indicator of microangiopathy in type 2 diabetic patients. METHODS: We analyzed 605 type 2 diabetic patients registered at a public health center in Korea. Following overnight fasting, venous blood and urine samples were collected and analyzed. The CCA-IMT, levels of carotid plaque, baPWV, and ankle-brachial index (ABI) of the subjects were assessed. We used non-mydriatic fundus photography to diagnose diabetic retinopathy. Multiple logistic regression analyses were used to evaluate the association between macroangiopathy and diabetic retinopathy. CCA-IMT and baPWV were divided into tertiles: CCA-IMT, 0.39 to 0.65 mm, 0.66 to 0.78 mm, and 0.79 to 1.30 mm; baPWV, 9.9 to 15.8 m/s, 15.9 to 18.9 m/s, and 19.0 to 38.0 m/s. RESULTS: The association between baPWV and diabetic retinopathy remained significant after adjustment, with an increasing odds ratio (OR) in the second tertile (OR, 2.41; 95% confidence interval [CI], 1.27 to 4.55) and the third tertile (OR, 4.63; 95% CI, 2.33 to 9.21). No significant differences were observed in carotid plaque, PAD, and each tertile of CCA-IMT. CONCLUSIONS: BaPWV was associated with diabetic retinopathy, while CCA-IMT, carotid plaque, and PAD were not. This study suggests that the association between macroangiopathy and microangiopathy may be attributable to functional processes rather than structural processes within the vascular system.